Determination of labile inorganic and organic species of Al and Cu in river waters using the diffusive gradients in thin films technique - Tonello, Paulo Sergio [UNESP]; Goveia, Danielle [UNESP]; Rosa, Andre Henrique [UNESP]; Fraceto, Leonardo Fernandes [UNESP]; Menegario, Amauri Antonio [UNESP] (Springer Heidelberg, 2011)
The diffusive gradients in thin films (DGT) technique, using a diffusive gel or a restrictive gel, was evaluated for the determination of labile inorganic and organic species of Al and Cu in model synthetic solutions and river water samples. Experiments were performed both in situ and in the laboratory. In the solutions containing Al ions, the major labile fraction consisted of inorganic species. The organic complex fractions were mainly kinetically inert. For the model Cu solutions, the most labile fraction consisted of inorganic species; however, significant amounts of labile organic complexes of Cu were also present. A comparison was made between the results obtained using restrictive gel DGT and tangential flow ultrafiltration (TF-UF). The Cu fraction determined by restrictive gel DGT (corresponding to the "free" ions plus the labile fraction of small molecular size complexes) was larger than that determined by TF-UF (corresponding to all small molecular size ions), suggesting that the techniques exhibited different porosities for discrimination of inorganic species. For the river water samples analyzed in the laboratory, less than 45% of the analytes were present in labile forms, with most being organic species. For the in situ measurements, the labile inorganic and organic fractions were larger than those obtained in the laboratory analyses. These differences could have been due to errors incurred during sample collection and storage. All results were consistent with those found using two different methods, namely, solid-phase extraction and the DGT technique employing the apparent diffusion coefficient.
Keywords: Diffusive gradients in thin films; Lability; Copper; Aluminum; Speciation